(untitled) (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2015)
The impact of terrorism on capital market of Pakistan has been examined in this research by using the ten biggest attacks of the last decade (with different targets and venue) out of a total of 941 attacks of this period. Event study methodology has been applied using one way ANOVA post-hoc and multivariate Regression techniques to investigate the impact of terrorist attacks on Karachi Stock Exchange. The results indicated that KSE is becoming insensitive to terrorist attacks. The assaults which target some important political figure and create countrywide violence can only disturb the functioning of KSE. The findings suggest that investors, unlike the stock exchanges of developed countries, should confidently invest at KSE because of numb behavior of market against terrorist attacks. However, the study has picked by only the biggest attack of every year, so future research can be made on all important attacks.